2019
DOI: 10.3389/fpsyt.2019.00349
|View full text |Cite
|
Sign up to set email alerts
|

Trust and Community Treatment Orders

Abstract: There are conflicting views about the benefits of community treatment orders (CTOs) for people with mental illness. While there is a significant literature on the coercive nature of CTOs, there is less on the impact that CTOs have upon trust. A recovery-oriented approach requires a trusting therapeutic relationship and the coercion inherent in the CTO process may make it difficult for trust to be built, nurtured, and sustained between workers and patients. Our aim was therefore to examine the role of trust wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…8,9 However, the coercive nature of supervised community treatment has caused much debate, with critics viewing CTOs as punitive, restricting civil liberties 10 and compromising trust in the patient–psychiatrist relationship. 11 A recent systematic review and meta-analysis found inconsistent evidence that compulsory community treatment improved patient outcomes. 12 It also confirmed findings from the only randomised controlled trial of CTOs in England, the Oxford Community Treatment Order Evaluation Trial (OCTET), that CTOs did not reduce rates of readmission.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, the coercive nature of supervised community treatment has caused much debate, with critics viewing CTOs as punitive, restricting civil liberties 10 and compromising trust in the patient–psychiatrist relationship. 11 A recent systematic review and meta-analysis found inconsistent evidence that compulsory community treatment improved patient outcomes. 12 It also confirmed findings from the only randomised controlled trial of CTOs in England, the Oxford Community Treatment Order Evaluation Trial (OCTET), that CTOs did not reduce rates of readmission.…”
Section: Introductionmentioning
confidence: 99%
“…CTOs were used by some clinicians to engage consumers in treatment, rather than spending the time required to develop trusting relationships (McMillan et al . 2019). At a systems level, a risk focus influences monitoring and reporting procedures, with compliance to risk assessment and management overriding other outcomes relevant to consumers (Szmukler & Rose 2013), such as reported jobs or social contacts.…”
Section: Discussionmentioning
confidence: 99%
“…Cath Roper, an Australian consumer academic, highlights that in the context of forced care, a person is ‘judged incompetent, owing to a lack of insight’ and subsequently dismissed as a person without equal status to clinicians. 38 (p. 420) Similarly, McMillan et al 21 found that clinicians did not fully trust consumers to understand their predicament and need for treatment, and thus pathologized any resistance that they expressed about the CTO and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Both theories are relevant to care planning for consumers on CTOs. CTOs can create distrust in the health care system and the clinicians and consumers within the system 21,22 . There are significant and valid justifications for consumers to have reduced trust at the interpersonal level (with clinicians) and the systems level (with services).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation